Location privacy preserving scheme against attack from friends in SNS - Xi LIN; Yi-liang HAN; Yan KE; Xiao-yuan YANG (Tongxin xuebao)
In order to enrich the performance of the user's location information and to meet the diverse needs of users,a location privacy protection scheme based on attribute encryption was designed,which provided precise,more accurate,fuzzy and private four modes to manage the location information.The scheme was based on the algorithm of WT-CP-ABE.The location information was divided into three parts according to a close friend of grade,then the key infor-mation and position information was encrypted with attribute-based encryption and symmetric encryption method respec-tively and the ciphertext was published to the social network.The security of the scheme is analyzed,which shows that the scheme has the advantage of user attribute information confidentiality,data confidentiality and can resist the collusion attack.